Faktor Yang Memengaruhi Perilaku Perawat Dalam Pemilahan Limbah Medis Di Ruang Rawat Inap Rumah Sakit Umum Sundari Medan - Dyna Safitri Rakhelmi Rangkuti; Andini Mentari Tarigan; Tiwi Amelia (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; Sundari Hospital Medan generates 762kg of medical waste yearly, with the inpatient room producing the most. Nurses segregate medical waste, both infectious and non-infectious, in violation of the provisions; this is thought to be due to factors such as knowledge, years of service, attitudes, the availability of facilities, and the use of less stringent sanctions. Purpose; The study examined the factors influencing nurses' behavior when sorting medical waste. Method; This research employed a descriptive method with a cross-sectional approach. The population was 52 inpatient nurses; all were taken as study samples. A questionnaire was used to collect data. The data was analyzed using univariate, bivariate, and multivariate analysis and the chi-square test. Result; The results showed that knowledge of values (0.03<0.05), years of service (0.043<0.05), attitudes (0.035<0.05), availability of facilities (0.025<0.05), availability of information (0.032< 0.05), policy (0.018 <0.05), has an effect on behavior in sorting medical waste because it is smaller than 0.05. Educational factors (0.249 <0.05) have no effect. The most influential variable is the policy with the value of Sig. 0.018. Conclusion; This study concluded that knowledge, years of service, attitudes, availability of facilities, information, and policies influence nurses' conduct when sorting medical waste. However, education has little effect. The policy was the most influential variable. The hospital should make and implement punishments for nurses who do not sort medical waste according to protocol; the hospital should arrange continual training/socialization, analyzes every month, and increase the number of medical waste sorting facilities.